Transcaval approach for endovascular aortic interventions: A systematic review. Issue 5 (November 2018) - Wee, Ian Jun Yan; Syn, Nicholas; Choong, Andrew M.T.L.
Highlights: Transcaval endoleak repair appears to be safe and effective. Transcaval transcatheter aortic valve repair is a feasible alternative. There is limited evidence on transcaval thoracic endovascular repair. It is important to consider individual patient factors when deciding vessel access. Abstract: The caval-aortic path is a novel access route for endovascular aortic interventions in aortic interventions, particularly for patients unsuitable for traditional access routes including femoral, subclavian, transapical, and aortic. A systematic review was conducted as per the PRISMA guidelines utilizing three electronic databases: Medline, Embase, and Cochrane database. There were 10 studies identified, including 7 retrospective studies, 1 prospective cohort study, and 2 case reports. Data on 209 patients (mean age 79.5 ± 5.1 years; 51.2% male) were abstracted including preoperative work-up, technical procedure details, and outcomes. The overall technical success rate for all procedures is 96.2%, with a 4.3% mortality rate and a mean follow up of 17.9 ± 19.8 months. Individually in the various interventions, the technical success rate of transcaval endoleak repair and transcatheter aortic valve implantation (TAVI) was 94.4% and 97.5% respectively, with a low 30-day mortality rate of 7.6% in the TAVI intervention. There is encouraging evidence regarding the rates of mortality and complications in the transcaval approach for endovascular aortic interventions. It presents a feasible alternative for a judiciously select group of patients who are not suitable for other access routes.